2022
DOI: 10.48048/tis.2023.6437
|View full text |Cite
|
Sign up to set email alerts
|

Duku (Lansium domesticum) Leaves Extract Induces Cell Cycle Arrest and Apoptosis of HepG2 Cells via PI3K/Akt Pathways

Abstract: Liver cancer is a type of malignant cancer that causes many deaths in the world. Efforts to find natural ingredients that can be used to treat liver cancer are very important. This study investigated the anticancer activity of ethanol extract of Duku (Lansium domesticum) leaves (LDE) through the cytotoxic activity, cell cycle inhibition mechanism and apoptosis influence through the PI3K/Akt pathways. Secondary metabolites of LDE were determined by common qualitative method. Cell cycle arrest was carried out by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
5
0
2
Order By: Relevance
“…The present study identified Annexin V positive cells as early-stage apoptotic cells, while Annexin V-PI double positive cells were identified as late-stage apoptotic cells. Necrotic cells were identified as PI single-positive cells ( Hasibuan and Sumaiyah, 2019 , Lubis et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…The present study identified Annexin V positive cells as early-stage apoptotic cells, while Annexin V-PI double positive cells were identified as late-stage apoptotic cells. Necrotic cells were identified as PI single-positive cells ( Hasibuan and Sumaiyah, 2019 , Lubis et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…Strong NaOH solution was one that had been used. Chitosan could still be ground to a certain size at this point, although it was still in the form of coarse granules [8]. The acetyl group (-NH-COCH3) of chitin was intended to be converted into an amine group (-NH2) in chitosan through a chitin deacetylation procedure using concentrated NaOH solvent.…”
Section: Deacetylationmentioning
confidence: 99%
“…Radikal bebas diproduksi dalam jumlah besar sebagai produk sampingan yang tak terhindarkan dari berbagai proses metabolisme, dan dalam kasus tertentu, seperti pada aktivasi neutrofil, akan menyebabkan meningkatnya radikal bebas dalam tubuh. Selanjutnya, radikal bebas dapat diproduksi dalam tubuh sebagai reaksi terhadap radiasi elektromagnetik dari lingkungan, dan dapat diproduksi secara langsung sebagai polutan pengoksidasi seperti ozon dan nitrogen dioksida (Lubis et al, 2023). Kerusakan dapat berkembang di berbagai jaringan jika antioksidan dalam tubuh lebih sedikit dibandingkan dengan jumlah radikal bebas.…”
Section: Pendahuluanunclassified
“…Kelompok kontrol negatif menunjukkan rata-rata kadar AST yang paling tinggi jika dibandingkan dengan semua kelompok. Ini disebabkan karena dosis APAP 800 mg/kg BB (Lubis et al, 2023), dapat menyebabkan kerusakkan hati yang ditandai dengan peningkatan kadar AST pada serum darah hewan tikus. Akibatnya efek kerusakkan sel hati pada kelompok kontrol negatif jauh lebih besar.…”
Section: Pengukuran Aspartate Aminotransferase Pada Serum Tikusunclassified